Comparison of the anxiety level between the medical staff and the public during the early phase of the coronavirus disease 2019 pandemic - Guanguan Luo; Yumin Liu; Dongai Yao; Shaozhou Ni; Bangsheng Wu; Liting Lin; Yunming Wang; Xiaoqing Jin (Emergency and Critical Care Medicine)
Abstract. Background. A sudden outbreak of the coronavirus disease 2019 (COVID-19) started in December 2019 in Wuhan, China. Up-to-date, there have been limited studies examining the anxiety status of Chinese individuals in the early phase of the pandemic period (January 30, 2020–February 15, 2020). This survey aimed to compare the level of anxiety of the medical staff with that of the public and to provide a theoretical basis for developing an effective psychological intervention. Method. Questionnaires were sent on the Internet (http://www.wjx.cn) during this period. The anxiety levels of Chinese people were investigated using the Self-Rating Anxiety Scale (SAS), and the demographic data were collected simultaneously. Results. A total of 1110 participants were enrolled in this study, with an effective response rate of 100%. A total of 482 respondents were medical staff (43.4%), while 628 were members of the general public (56.6%). The medical staff itself had a higher SAS score than the general public (48.36±13.40 vs. 45.74±11.79, P < 0.01), while the medical staff in Wuhan were more anxious than the public in Wuhan with a higher SAS score (54.17±14.08 vs. 48.53±11.92, P < 0.01). Conclusion. The COVID-19 pandemic has had a significant impact on the anxiety levels of the medical staff and the public, with the medical personnel showing a higher anxiety level than the public, especially female medical staff in Wuhan. Therefore, urgent intervention programs to reduce anxiety should be implemented.